Manipulação de eletrólitos na dieta de poedeiras em fase de declínio de postura em condições de altas temperaturas - Neves, Fabiano Almeida [UNESP] (2015)
One metabolic disease that affects the layers hens is the acid-base disturbance. This disorder, which is aggravated by heat stress, consisting of an increase in blood pH, leading to respiratory alkalosis, thus compromising the performance and egg quality. To minimize this problem it is possible to manipulate the diet of the poultry, favoring balance and electrolyte ratio and hence reduce losses, mainly related mortality and fragility of the eggshell, events easily observed decline in layers hens production. Thus, the present study evaluated the effects of manipulation of electrolytes in the diet on the performance, egg quality and economic viability of laying hens in the decline phase of production in high temperature conditions. In the handling of electrolytes considered different electrolyte balance (Na + + K + - Cl - ) and different electrolytic relations [(K + + Cl - ) / Na + ]. 288 laying hens were distributed by a design in random blocks in a factorial 4 x 3 (4 electrolyte balance 140, 210, 280 and 310 mEq/kg x 3 electrolytic relations 2:1, 2.5:1 and 3:1) totaling 12 treatments with four replicates of six poultry each. Experimental diets were formulated by nonlinear programming free software. The experiment lasted for 3 cycles of 28 days each and the results were submitted to analysis of variance. In case of significance, the Tukey test at 5 % probability, compared the means. For the performance of laying and economic viability no effect on electrolyte balance and electrolyte ratio were found, but the BE of 280 mEq / kg demonstrated best values. For egg quality observed significant differences in electrolyte ratio in the parameters of yolk percentage and Haugh unit, and cycle, all parameters where the balance of 140 mEq / kg and 2 compared to 2.5, independent of interactions, demonstrated best indices of egg quality